(untitled) (Modern information system and technologies, 2018)
In the analysis of the characteristics and properties of quadrature amplitude modulation (QAM) systems, a method was proposed that is based on the modification of the QAM constellation to increase the noise immunity, which increases the total amount of information transmitted in the channel. The basis is considered convolution codes, namely the Viterbi algorithm.